Metodologias para a avaliação do potencial fisiológico de sementes de tabaco - Crivellari, Renata Pereira Luz (2016)
Despite tobacco being a culture propagated by seeds, there is little information concerning tests that allow the distinction of similar germination lots in different levels of vigor. The diversity of cultivars available in the market, and a few peculiarities of the species, such as uneven maturation of the flowers, fruits and seeds, small size and seed dormancy, are considered obstacles for obtaining lots of tobacco of high physiological potential. Thus, this research was developed with the objective of adapting feasibility and vigor tests for evaluating the physiological potential of tobacco seed lots. We used nine lots of tobacco seeds of cultivar CSC 447 and nine lots of seeds of cultivar BAT 2101, belonging to variety groups Virginia and Burley, respectively. Initially, germination test was conducted to characterize the profile of the lots. For determining the feasibility and vigor of the tobacco seeds, germination tests were conducted in distinct temperatures, controlled emergence conditions, electric conductivity, artificial aging and in tetrazolium. For determining the isoenzymatic marker for seed quality, analyses were conducted with enzymes catalase, esterase, malate dehydrogenase and alcohol dehydrogenase. In conclusion, the emergence tests at 25oC and artificial aging at 41oC for 72 hours, are efficient in discriminating the lots of tobacco seeds in different levels of vigor. The electric conductivity and germination tests in different temperatures have distinct responses in relation to the genotype of the tobacco seeds. The tetrazolium test using the methodology with pre-conditioning in 3.5% sodium hypochlorite solution and subsequent emersion in 1.0% tetrazolium solution for 18 hours is efficient for the quick evaluation of the feasibility of tobacco seeds. The analysis of the profiles of enzymes catalase, esterase, malate dehydrogenase and alcohol dehydrogenase is efficient as markers for tobacco seed quality.